Mental Resilience of Crime Scene Investigators: How Police Officers Perceive and Cope With the Impact of Demanding Work Situations - Sollie, Henk (Criminal justice and behavior, 2017)
This study provides an in-depth analysis of the resilience of crime scene investigators (CSIs) in the Netherlands and how they perceive and cope with daily work stressors. Observational studies within five CSI teams and 35 semistructured interviews with investigators revealed that administrative accumulation, long and irregular working hours, confrontations with human suffering, decision making, and dirty and physically demanding circumstances at the crime scene can be very stressful. By employing strict management of thoughts, visualization, focus on sensemaking, sharing of emotions and responsibilities, and avoiding potentially distressing working situations, CSIs overcome the strain of forensic investigations. However, successful implementation of these resilience-enhancing strategies depends on the availability of several individual, team, and organizational resources. To reduce the risk of health problems and to stimulate positive functioning, these resources require permanent investment by police management and CSIs themselves.